Investigating Effects of Viral Marketing on Consumer’s Purchasing Decision (Case Study: The Students of the Administrative Sciences College- Najran University) - Mohammed Mohammed Ali Hamed, Eltaj (British Journal of Marketing Studies, 2017)
The study aims to examine the effects of viral marketing on consumers purchasing decision among the students of administrative science college at Najran University. The population of this study is consisted of all the students of administrative science college at Najran University, which is according to the latest data, a number of 710 individuals. In order to measure the variables used in this research, a questionnaire was used. Validity of the above-mentioned questionnaire was confirmed by experts and their reliability were measured using Cronbach’s alpha coefficient that was respectively 0.697. Also, Statistical methods were used for the analysis of final descriptive and inferential statistics (methods like one-way sample test). The findings showed that there is a significant and positive relationship between the viral marketing and the purchase decision; In other words, viral marketing leads costumers to improve their purchase decisions.